2010
DOI: 10.1096/fj.09-145102
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/ROCK signaling is essential for multiple aspects of VEGF‐mediated angiogenesis

Abstract: The small GTPase RhoA and its downstream effectors, ROCK1 and ROCK2, regulate a number of cellular processes, including cell motility, proliferation, survival, and permeability. Pharmacological inhibitors of the Rho pathway reportedly block angiogenesis; however, the molecular details of this inhibition are largely unknown. We demonstrate that vascular endothelial growth factor-A (VEGF) rapidly induces RhoA activation in endothelial cells (ECs). Moreover, the pharmacological inhibition of ROCK1/2 using 10 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
219
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(243 citation statements)
references
References 64 publications
19
219
2
3
Order By: Relevance
“…We have previously demonstrated that ablation of ROCK1 & 2 kinase activity with the non-selective ROCK1 & 2 pharmacological inhibitor Y27632 resulted in disrupted angiogenesis [7]. To determine the contribution of the individual ROCK paralogs to capillary network formation, the endothelial cell panel stably overexpressing non-targeting, ROCK1, or ROCK2 shRNA plasmids was subjected to matrigel network formation assays.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously demonstrated that ablation of ROCK1 & 2 kinase activity with the non-selective ROCK1 & 2 pharmacological inhibitor Y27632 resulted in disrupted angiogenesis [7]. To determine the contribution of the individual ROCK paralogs to capillary network formation, the endothelial cell panel stably overexpressing non-targeting, ROCK1, or ROCK2 shRNA plasmids was subjected to matrigel network formation assays.…”
Section: Resultsmentioning
confidence: 99%
“…MS1 mouse pancreatic endothelial cells (ATCC# CRL-2279), SVR mouse engineered angiosarcoma cells (ATCC# CRL-2280), and B16F1 mouse melanoma cells (ATCC# CRL-6323) were maintained in Dulbecco’s modified Eagle’s media (DMEM) supplemented with 10% fetal bovine serum (FBS), 80 U/ml penicillin, and 50 µg/ml streptomycin C. Cells were treated as indicated with the following concentrations: human recombinant VEGF 165 (VEGF) (2.5 ng/ml) or Y27632 (10 mM) as previously described [7]. shRNA vectors (SABiosciences) (Table 1 ) were transfected using Lipofectamine 2000, and cell pools were stably selected with hygromycin ( MS1 cells ) or puromycin ( SVR cells ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations